Impacts of extreme drought and heatwave events on evergreen forests in warm and humid climate regions - Yangfei Ge; Mijun Zou; Yali Ding; Weijia Jia; Jiale Shen; Rui Liu; Wenpeng Lin (Environmental Research Letters, 2025)
Afforestation and reforestation are widely recognized as key ecological approaches for addressing global warming. However, the increasing frequency, duration, and intensity of extreme climate events, especially in warm and humid regions, pose great challenges to the carbon sequestration efficiency and ecological stability of forest ecosystems. Consequently, understanding the different performances of planted versus natural forests under extreme conditions in such vulnerable regions is urgently needed. This study investigated the impacts of drought and heatwave events on the gross primary productivity (GPP) and water use efficiency (WUE) of natural and planted evergreen forests. The response of ecological stability to event intensity and duration was assessed by anomalies, and resistance and resilience were calculated using the GPP and WUE, respectively. Our findings revealed that (1) GPP anomaly was more sensitive to heatwaves, whereas WUE anomaly was more sensitive to drought in both forest types; notably, natural forests presented smaller GPP and WUE anomalies during extreme events; (2) natural forests presented superior resistance across varying intensities and durations, whereas planted forests generally presented greater resilience; and (3) threshold comparisons indicated that natural forests could withstand more intense drought and heatwaves. In terms of duration, natural forests presented greater resistance to drought events lasting up to three months, whereas planted forests presented greater resilience to heatwave events lasting more than two months. These findings provide valuable insights and guidance for forest management under climate extremes and contribute to a more reliable foundation for strategies to mitigate global warming.